Maps and plans illustrative of Thucydides. - Neele, Josiah, engraver. (Tufts University. Tisch Library., 2018)
1 online resource (1 atlas (37 unnumbered leaves of plates)) : illustrations, maps.; Maps engraved by J. Neele, sc. 352 Strand, and published by J. Vincent, Oxford.; Most maps are double plates.